Detaching graphene from copper substrate by oxidation-assisted water intercalation. (March 2016) - Wu, Ruizhe; Gan, Lin; Ou, Xuewu; Zhang, Qicheng; Luo, Zhengtang
Abstract: For electronic applications, graphene prepared by chemical vapor deposition (CVD) are required to be detached from the catalytic substrate, while retaining structural integrity. We demonstrate that CVD grown graphene on copper can be fully decoupled from the substrate by immersion in water, without significant damage to graphene. We find that the decoupling starts from the graphene edges and defect sites, assisted by interfacial copper oxidation and water intercalation due to galvanic corrosion. Kinetics study reveals the activation energy of 0.3 ± 0.08 eV for this decoupling process, and interfacial oxidation acts as the dominating role. This facile water-immersion method can be extended to adjust the interaction between graphene and metals, and assist our understanding of interfacial chemistry in confined space.